2023
DOI: 10.3389/fpsyt.2023.1219049
|View full text |Cite
|
Sign up to set email alerts
|

Case report: Impact of hyperthyroidism on psychotic symptoms in schizophrenia comorbid with Graves’ disease

Abstract: IntroductionAuditory hallucinations are the most common type of hallucinations observed in schizophrenia; however, visual hallucinations are not uncommon. In Graves’ disease, depression, hypomania, and psychosis can occur. While the association between Graves’ disease and psychosis has been explored, understanding of the specific impact of thyroid dysfunction severity on psychiatric symptom severity is limited. Here, we present a case report of a patient with schizophrenia comorbid with Graves’ disease whose p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
(49 reference statements)
0
1
0
Order By: Relevance
“…Consequently, the levels of thyroid hormones also increase due to the heightened TSH activity. Previous investigations have established links between thyroid hormone levels and the manifestation of psychotic symptoms [ 53 56 ]. Duval et al postulated that thyroid dysfunction observed in patients with psychotic disorders may stem from heightened cortisol secretion triggered by an overactive hypothalamic-pituitary-adrenal axis [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the levels of thyroid hormones also increase due to the heightened TSH activity. Previous investigations have established links between thyroid hormone levels and the manifestation of psychotic symptoms [ 53 56 ]. Duval et al postulated that thyroid dysfunction observed in patients with psychotic disorders may stem from heightened cortisol secretion triggered by an overactive hypothalamic-pituitary-adrenal axis [ 52 ].…”
Section: Discussionmentioning
confidence: 99%